How an emotional intelligence intervention programme impacts the well-being and performance of teachers of basic general education - Wendy L. Arteaga-Cedeño; Miguel Á. Carbonero-Martín; Luis J. Martín-Antón; Paula Molinero-González; Lorena Valdivieso-León (Acta Psychologica)
Emotional education helps to develop emotional intelligence skills and to bolster teachers' overall well-being. Aims: to gauge the effectiveness of the programme designed to enhance the emotional intelligence, life satisfaction, life orientation, and work well-being of teaching staff. A quasi-experimental design was employed with an experimental group and a control group, using pre-test and post-test to measure changes. Method: 425 teachers of basic general education from Ecuador took part. The experimental group participated in an intervention programme in emotional intelligence during one term, while the control group were not subject to any intervention. An array of instruments were used to measure the variables of interest before and after intervention. Results: significant improvements emerged in emotional intelligence factors in the experimental group compared to the control group. Significant increases were seen in life satisfaction, optimism, feeling energy, enthusiasm, and immersion, and there was reduced pessimism. Women improved more in emotional perception, while men evidenced greater improvement in understanding and emotional regulation. A positive correlation was found between the study variables. Conclusions: these findings highlight the importance of implementing emotional education programmes in teacher training in order to promote a healthier and more effective educational environment.